O planejamento estratégico do capital humano como fator de desenvolvimento sustentável das organizações na agroenergia: estudo de caso - Paternostro Neto, Francisco (2010)
The objective of this thesis is to analyze, guide and indicate some forms of measuring the results of actions or programs in the area of Human Resource Management along the years, as well as for the new tendencies in the sector of agro-energy. The task also tries to propose practices of strategic planning and benchmarks for organizations, focusing on the development and in the envisioned changes in such organizations, in the labor markets, in the management models and in the business of the sugar cane production segment, for the coming years. The study analyzes organizational transformations, new competitive challenges – present and future, and the way the area of Human Resources in several of the organizations of the sector have kept up with such a process, and the impact of such actions in a context of changes in the processes of the agricultural chain (soil mechanization, harvest, among others), and industrial chain (biorefineries, second generation ethanol, gasification… among others), and in the organizational and human development as an integral part of a program of sustainability of organizations. Methodologies, systems and tools of strategic planning are also dealt with, as well as the measuring proposed by some authors who intend to demonstrate, in an integrated form, the impact of the strategies and actions of Human Resource Management in the direction of the achieving of goals and objectives of organizations, in a background of intense internal and global growth of the bioenergy market. In such a scenario, a discussion and an exposition of how companies in the sugar-alcohol sector make practical use of such methodologies is made, besides the dealing with the performance indicators of the sector in comparison to the needs, so that an indication of the best practices and tools can be made, in order to facilitate the decision processes, the use of Human Resource metrics for the forecast and follow-up of the Human Capital, the optimizing of the resources and investments as they relate to the new challenges of the sector. Even though new initiatives aiming at transforming the Human Resource Management into a strategic factor for agro-energy organizations can be seen, the survey identified that the Human Resource area is demonstrating evolution in that direction, and that it can effectively contribute for better performance and for the sustainability of business.